Prevalence of under-nutrition and its associated factors among 6–23 months old children of employed and unemployed mothers in town kebeles of Dera district, northwest Ethiopia: a comparative cross-sectional study - Habtamu Zelalem; Yeshalem Mulugeta Demilew; Samuel Dagne; Anteneh Mengist Dessie (BMC Nutrition, 2023)
Abstract Background Child under-nutrition remains a widespread problem around the globe. Improving child nutrition and empowering women are two important and closely connected development goals. These two interconnected goals will affect one another through different mechanisms, and the net effect may not necessarily be positive. Yet, the impact of maternal employment, one method of empowering mothers, on children’s nutritional is not well studied in Ethiopia. Hence, this study is to compare the prevalence of under-nutrition and its associated factors among 6–23 months old children of employed and unemployed mothers in town kebeles of Dera district, Northwest Ethiopia, 2022. Methods A community-based comparative cross-sectional study design was conducted among 356 employed and 356 unemployed mothers having 6–23 months old children. A systematic random sampling technique was used to select study participants. Epi-data version 3.1 and SPSS version 25.0 statistical software were used for data entry and analysis, respectively. Both bi-variable and multivariable binary logistic regression was done to assess the association between independent and dependent variables. A p-value of less than 0.05 in a multivariable binary logistic regression was declared as the level of statistical significance. Result The prevalence of under-nutrition was 69.8% (95% CI: 65.0, 74.7) among children of unemployed mothers, compared to 27.4% (95% CI: 22.7, 32.2) among children of employed mothers. Under-nutrition among children of unemployed mothers was significantly associated with being a male child, age increase by one month, household food insecurity, lack of ANC follow-up, and not exclusively breastfed. Whereas, among children of employed mothers, being a male child, age increase by one month, being sick during the last two weeks prior to data collection, not immunized to their age, and low meal frequency were significantly associated with their under-nutrition. Conclusion The prevalence of under-nutrition among children of unemployed women is significantly higher than those children of employed women which consolidate the evidence that women’s employment status have a positive association with child nutrition. Different factors were also identified as significant predictors of child under-nutrition among these two groups (employed and unemployed women). Thus, multi-sectoral intervention approach together with agriculture and education offices should be strengthened.